Intramolecular C–O Insertion of a Germanium(II) Salicyl Alcoholate: A Combined Experimental and Theoretical Study. Issue 33 (28th October 2015) - Kitschke, Philipp; Rüffer, Tobias; Korb, Marcus; Lang, Heinrich; Schneider, Wolfgang B.; Auer, Alexander A.; Mehring, Michael
Abstract: The synthesis of germanium(II) 2‐ tert ‐butyl‐4‐methyl‐6‐(oxidomethyl)phenolate (1 ) starting from Ge[N(SiMe3 )2 ]2 and the corresponding salicyl alcohol is reported. Compound 1 undergoes an intramolecular oxidative insertion reaction of germanium into a C–O bond to result in a cyclic germanium(IV) tetraoxidogermocane (2 ). Addition of 3‐ tert ‐butyl‐2‐hydroxy‐5‐methylbenzyl alcohol to either compound 1 or 2 gave a spirocyclic monoorgano dioxagermine (3 ). The results of 1 H NMR spectroscopic studies and DFT‐D calculations are in agreement with the proposed reaction cascade in which the novel germylene 1 is first converted into the germocane 2 followed by reaction with 3‐ tert ‐butyl‐2‐hydroxy‐5‐methylbenzyl alcohol to finally provide compound 3 . Addition of 4‐(dimethylamino)pyridine to a solution of germylene 1 resulted in the formation of an air‐stable monomeric 1:1 complex (4 ). The characterization of compounds 1 –4 by single‐crystal X‐ray diffraction analysis, thermal analysis, and 1 H NMR, 13 C{ 1 H} NMR, and ATR‐FTIR spectroscopy is presented. Abstract : Germylene 1 underwent an intramolecular oxidative insertion of Ge into a C–O bond in solution to give cyclic germocanes 2 . Addition of 3‐ tert ‐butyl‐2‐hydroxy‐5‐methylbenzyl alcohol to 1 or 2 gave spirocyclic dioxagermine 3 . 1 H NMR analysis and DFT calculations concur with the proposed reaction cascade. Intermolecular stabilization of 1 upon addition of DMAP provided a stable monomeric 1:1 complex.